Terminalia chebula Retz. (Harad) for Livelihood Security of Farmers of Kandi Villages of Jammu Region of Jammu and Kashmir - Choudhary, Punit; Rakesh,; Gularia, Vipin; Gupta, S. K.; Tandon, Vikas; Arora, R. K. (Indian Forester, 2019)
Farmers of Kandi villages of Jammu adopted themselves to traditional Harad based agro-forestry practices servers as livelihood security for the resource poor farm families of the villages.The average yield per tree was recorded to be 100-120 kg, whereas there are reports of trees bearing 5-7 quintals of fruits/tree generating an average income of â‚¹1600-2000 per tree per year. A superior genotype named Raj Harad have been found existing in Mathwar block of Jammu district for over 100 years having height of 14.70 m, diameter at breast height of 101.81 cm2 with crown width of 18.50m bearing fruits of average weight of 44.60gm. About 7000-8000 wild/planted Harad trees in Mathwar block alone have a green and dry fruit production trade of more than 350 Tonnes and 15-20 Tonnes respectively, that is being exported to Pakistan and gulf countries through Amritsar border fetching a total income of more than 40 lakhs per annum. With coming up of superior grafting clones of Harad, the expected economic returns from these grafted clones at an early bearing age of 7-8 years will â‚¹593750 per ha that will be almost double than the existing seedling plantations.